PENGARUH ADVERSITY QUOTIENT DAN IKLIM KELAS TERHADAP PRESTASI BELAJAR EKONOMI SISWA KELAS X SMAN 3 PARIAMAN - Wildanul Husna (Universitas Negeri Padang, 2018)
Abstract: This research aims to determine the influence of adversity quotient and classroom climate on students' economic achievement. The type of this research are descriptive and associative. The population of this research are the tenth grade students of SMAN 3 Pariaman who study economic subjects and enrolled in academic year 2017-2018 which amounted to 192 students, the sample of this reasearch are 129 students. The sampling technique is done by Proportional Random Sampling. Questionnaire is used as a data collection tool. Data analysis technique used is multiple linear regression. The results showed that there was a significant positive effect between adversity quotient and classroom climate on students' economic achievement. Based on the results of the research, it was suggested for students to further increase adversity quotient and form a good classroom climate in learning in order to get a more optimal achievement. For the teachers, they are expected to pay more attention to the condition of students in learning, and for parents, they are expected to pay attention to the development of their children, so they can provide encouragement to students to remain eager in learning in order to get better learning achievement.Keyword: adversity quotient, classroom climate, learning achievement